Self Care of Mental Health Generation Z Of Melanesia Race In Indonesia - Behuku, Freodisa Meilisa; Alfianto, Ahmad Guntur; Amalia, Waifti (Journal of Rural Community Nursing Practice, 2023)
Generation Z is the generation with an average age of 10 to 25 years. This generation is smarter and more active in digitalization than the previous generation. Mental health problems in Generation Z have increased every year. Efforts made by doing mental health self-care. One of the races in Indonesia, mental health problems often occur. The race is the Melanesian Race which is in the eastern part of Indonesia. Cultural factors and warfare have contributed to mental health problems in the region. This research aims to describe mental health self-care for Melanesians in Indonesia. This research design uses a quantitative descriptive research design with a survey approach. The sample used is Generation Z of the Melanesian Race with a total of 169 respondents. The sampling technique used is purposive sampling. The measuring tool uses the Mindful Self-Care Scale questionnaire. The sampling technique is by distributing it through the Google form, Whatsapp groups, telegrams to social media. The research was conducted from September 2022 to February 2023. The description of the average mental health self-care for Generation Z of the Melanesian Race is mostly physical care (17.56 ± 4.986). while self-care mental health generation Z Race Melanesian (82.13±16.021). Mental health self-care for generation Z Melanesian race prefers physical care. And self-care for the mental health of Generation Z of the Melanesian Race is more towards positive behavior.